Improving Students' Knowledge About The Importance Of Physical Activity Through Health Counseling At Mts Al Madani Sasak Panjang Bogor School - Nabila Amelia Kirani; Alyda Kausy; Nabila Fitri Ramadhani (CV. AFDIFAL MAJU BERKAH, 2026)
Lack of physical activity among adolescents is becoming an increasingly worrying global health problem. WHO data (2022) shows that more than 80% of adolescents worldwide are not physically active enough, while the 2018 Basic Health Research (Riskesdas) recorded that 33.5% of Indonesia's population aged ≥10 years were physically inactive, with West Java reaching 37.5%. This study aims to determine the increase in students' knowledge about the importance of physical activity through health education based on the Health Belief Model (HBM) at MTs Al Madani Sasak Panjang, Bogor Regency. The study used a descriptive qualitative approach with pre-test and post-test questionnaire instruments administered in May 2026 to 9th grade students. The results showed an increase in three HBM components: perceived susceptibility increased from 23 to 26, perceived severity from 27 to 28, and perceived barriers from 18 to 22. Meanwhile, perceived benefits did not change (remained at 44), indicating a ceiling effect because students already had a fairly good understanding of the benefits of physical activity before the intervention. The largest improvement occurred in the perceived barriers component, indicating students were increasingly aware of real barriers such as limited time, laziness, lack of facilities, and the influence of device use. It was concluded that HBM-based health education was effective in increasing students' awareness of the risks and barriers to physical activity. Schools are advised to make this program a routine and ongoing activity, with concrete strategies to address the identified barriers.